2016
DOI: 10.1016/j.conbuildmat.2016.03.070
|View full text |Cite
|
Sign up to set email alerts
|

Influence of different fibers on the change of pore pressure of self-consolidating concrete exposed to fire

Abstract: The focus of this paper is given to investigate the effect of different fibers on the pore pressure of fiber reinforced self-consolidating concrete under fire. The investigation on the pore pressure-time and temperature relationships at different depths of fiber reinforced self-consolidating concrete beams was carried out. The results indicated that micro PP fiber is more effective in mitigating the pore pressure than macro PP fiber and steel fiber. The composed use of steel fiber, micro PP fiber and macro PP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 100 publications
(49 citation statements)
references
References 19 publications
3
46
0
Order By: Relevance
“…These results show that specimens with metallic fiber addition have suffered the fire action more intensely than the specimens without addition or with polypropylene fibers. These results agree with other research results published, where it is proved that in concrete subjected to high temperatures, the addition of steel fibers increases concrete porosity but to a lesser extent than in the case of the addition of polypropylene fibers, reducing pressure in the pores in the deeper concrete areas, and contributing to the confinement of dehydrated [28,41,42]. The addition of polypropylene fibers in concrete, when the melting point is reached (170°C), creates a series of channels in the concrete mass that allows water vapor to evacuate, releasing pore pressure, gradually reducing the temperature, and decreasing the cracks in the cooling phase [25,27,43].…”
Section: Results and Analysissupporting
confidence: 83%
See 1 more Smart Citation
“…These results show that specimens with metallic fiber addition have suffered the fire action more intensely than the specimens without addition or with polypropylene fibers. These results agree with other research results published, where it is proved that in concrete subjected to high temperatures, the addition of steel fibers increases concrete porosity but to a lesser extent than in the case of the addition of polypropylene fibers, reducing pressure in the pores in the deeper concrete areas, and contributing to the confinement of dehydrated [28,41,42]. The addition of polypropylene fibers in concrete, when the melting point is reached (170°C), creates a series of channels in the concrete mass that allows water vapor to evacuate, releasing pore pressure, gradually reducing the temperature, and decreasing the cracks in the cooling phase [25,27,43].…”
Section: Results and Analysissupporting
confidence: 83%
“…In the case of the addition of polypropylene fibers, the ability to reduce cracking is due to fact that concrete permeability increases suddenly between 80°C and 130°C, and polypropylene, once it has reached the melting point, flows through the cracks and produces channels allowing the water vapor and gases to be evacuated releasing the pore pressure [20][21][22][23][24][25][26][27][28]. Although there are numerous research works on the behavior of concrete elements to fire, no literature has been found about concrete elements subjected to compression in the range of temperatures studied in the present work, neither when subjected to a direct fire test, nor comparisons performance to fire of concrete with steel and polypropylene fibers.…”
Section: Introductionmentioning
confidence: 99%
“…An empirical formula is proposed in [31] for predicting the relative maximum pore pressure in concrete with the addition of fibrous materials exposed to fire.…”
Section: Figure 1 Explosive Spalling Of Concretementioning
confidence: 99%
“…Besides, addition of steel fibers plays an important role in moisture migration. It has been reported that addition of 50 kg/m 3 of steel fibers in self-consolidating concrete could reduce pore pressure during one-dimensional heating tests (Ding, Zhang, Cao, Zhang and Azevedo 2016). It was hypothesized that steel fibers entrapped air bubbles which act as reservoirs to accommodate water vapor and the vapor pressure may be relieved through weak ITZs around the steel fibers.…”
Section: Steel Fibersmentioning
confidence: 99%
“…Moreover, the combined use of PP and steel fibers to prevent explosive spalling of fiberreinforced self-consolidating concrete (FRSCC) and HSC subjected to elevated temperature has been investigated Horiguchi 2012, Ding, Zhang, Cao, Zhang andAzevedo 2016). Shallow flaking of concrete cover was observed, and release of pore pressure was reported in the literature.…”
Section: Pp Fibersmentioning
confidence: 99%